Distal retrieval of dislodged and migrated guidewires after retrograde puncture of the deep femoral and dorsal pedal artery. A case series - Korosoglou, Grigorios; Giusca, Sorin; Antaredja, Muliadi; Schmidt, Andrej; Blessing, Erwin (Clinical Case Reports, 2021)
We report on retrograde retrieval of the soft end of dislodged guidewires during complex interventions. Interventionalists may consider this as an option for the endovascular management of this complication if an antegrade retrieval is not possible or fails.